Leveraging Artificial Intelligence to develop the presenting skills in Arabic language learning - Mulyani, Slamet; Habibah, Ihda Filzafatin; Mukarom, Arik Maghfirotul; Suja, Aidillah; Akhirudin (Proceeding International Conference on Education, 2023)
The development of the industrial revolution has led us to the society 5.0 era, where the integration of digital technology into people’s lives was inevitable. Therefore, this study explores the opportunities of leveraging Artificial Intelligence (AI) to develop presenting skills in Arabic language learning while examining how teachers can mitigate the challenges and negative implications. We employ the interpretivism research paradigm with a qualitative approach and library research method. Data was collected through documentation techniques and analysed using Miles & Huberman’s interactive analysis model during and after data collection, following the characteristic of the qualitative research data analysis approach. The study’s outcomes offer two valuable things: firstly, a comprehensive understanding of the challenges and opportunities of leveraging AI in Arabic language learning, and secondly, practical strategies for successfully integrating AI into the learning process. Consequently, the results are expected to significantly improve students’ engagement and learning outcomes in Arabic language learning, particularly in developing presenting skills.